2000
DOI: 10.1029/1999gl008401
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mineral bond strength and adsorbed water on fault gouge frictional strength

Abstract: Abstract. Recent studies suggest that the tendency of many fault gouge minerals to take on adsorbed or interlayer water may strongly influence their frictional strength. To test this hypothesis, triaxial sliding experiments were conducted on 15 different single-mineral gouges with various water-adsorbing affinities. Vacuum dried samples were sheared at 100 MPa, then saturated with water and sheared farther to compare dry and wet strengths. The coefficients of friction, g, for the dry sheet-structure minerals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
240
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(272 citation statements)
references
References 14 publications
(14 reference statements)
27
240
1
2
Order By: Relevance
“…Saffer and Marone, 2003] For illite shale the coefficient of sliding friction ranges from 0.41 -0.63 over the range of normal stresses. These values are consistent with previous work on clays and clay shales [Logan and Rauenzahn, 1987;Morrow et al, 1982;Morrow et al, 1992;Morrow et al, 2000]. Illite shale has nearly the same failure envelope as quartz and each exhibits a constant angle of internal friction over this range of normal stresses ( fig.…”
Section: Frictional Strength Of Illite Shale Smectite and Quartz-smsupporting
confidence: 81%
See 2 more Smart Citations
“…Saffer and Marone, 2003] For illite shale the coefficient of sliding friction ranges from 0.41 -0.63 over the range of normal stresses. These values are consistent with previous work on clays and clay shales [Logan and Rauenzahn, 1987;Morrow et al, 1982;Morrow et al, 1992;Morrow et al, 2000]. Illite shale has nearly the same failure envelope as quartz and each exhibits a constant angle of internal friction over this range of normal stresses ( fig.…”
Section: Frictional Strength Of Illite Shale Smectite and Quartz-smsupporting
confidence: 81%
“…The frictional strength of pure smectite has been shown to decrease with saturation, by as much as a factor of 2 [Morrow et al, 1992[Morrow et al, , 2000. In contrast, Morrow et al [1992] showed that the coefficient of sliding friction for illite shale is not appreciably affected by saturation, consistent with the fact that illite is not a hydrous clay mineral.…”
Section: Frictional Behavior Of Illite Shale Smectite and Quartz-smmentioning
confidence: 72%
See 1 more Smart Citation
“…Strangely, XRD analysis shows that this sample is composed of only $35% phyllosilicates, while the amounts of zeolite (15%) and iron oxides (e.g., hematite, 7%) could be significant. Studies investigating the frictional strength of zeolites are rare; however, the friction of the zeolite species laumontite and clinoptilolite was measured to be 0.66 to 0.80 under water-saturated conditions and thus would not be a source of weakness [Morrow and Byerlee, 1991;Morrow et al, 2000]. We are currently unaware of studies measuring the frictional behavior of iron oxides.…”
Section: Lithologic/mineralogic Controls On Observed Strength Patternsmentioning
confidence: 99%
“…That explanation does not seem likely, at least for crustal faults, as measurements of pore pressure within Earth's crust generally indicate hydrostatic conditions [Townend and Zoback, 2000], even in the SAF itself [Zoback et al, 2010]. Other theories appeal to anomalously low frictional resistance, from either frictionally weak clayrich materials [Morrow et al, 2000;Carpenter et al, 2011] or weak fault zone fabrics [Collettini et al, 2009] at seismogenic depths. Weak materials occur within the creeping section of the SAF and appear to be the most likely explanation for its weakness, but that cannot explain the similarly low stresses on other seismogenic parts of the SAF.…”
Section: Introductionmentioning
confidence: 99%